Advances in drug delivery for post-surgical cancer treatment. (October 2019) - Bu, Lin-Lin; Yan, Junjie; Wang, Zejun; Ruan, Huitong; Chen, Qian; Gunadhi, Vivienne; Bell, R. Bryan; Gu, Zhen
Abstract: Surgery remains a primary modality of treatment for the majority of solid tumor malignancies. While advancements in surgical technique and instrumentation have improved the quality of life for cancer patients, local tumor recurrence and metastasis after surgery remain challenging and result in a high rate of mortality and decrease quality of life. It is therefore urgent to explore effective methods to eliminate residual microscopic disease in the surgical site and/or circulating tumor cells (CTCs) to inhibit tumor recurrence and minimize the risk of distant metastasis. Recently, advances in bioengineering technology have facilitated the development of drug delivery systems (DDSs) for the release of chemotherapy and immunotherapy agents, which could be used to enhance the effectiveness of surgical resection. In this review, we survey the rapidly evolving fields of local and systemic controlled DDSs, utilizing a variety of formulations and devices, such as implantable wafers, injectable/sprayable hydrogels, micro/nanoparticles, and cellular particles. Opportunities and challenges for the clinical translations of these delivery systems are also discussed.